The Effect of Using Infographic on Students’ Writing Summary Skill - Ayu Fitriani; Melyann Melani; Leli Lismay (Universitas Pahlawan Tuanku Tambusai, 2021)
This research was due some of problems in the English learning process. Firstly, the students had difficulties in writing summary because the students did not have the skill to writing summary. The students did no how to begin writing summary. Secondly, teacher seldom used media in learning English. And thirdly, the students had poor vocabulary mastery. This research used quantitative descriptive research. The data was taken through the test. The population in were 92 students of XI TKJ 30, XI KC2 26 and XI PH 36 students.. The researcher used purposive sampling. Because only one class that is taught by the teacher with giving feedback. It is class XI TKJ 2 which consist of 30 students. Based on the results of the research, the finding reveals that students used infographis with result (2,177%) was higher than t-table (1,673%) , there was significant effect of using infographic on students writing summary. Then, the result of post-test both classes experimental and control class was obtained (2,163%) which was higher than t-table(,637%). So that, the students who are taught by using infographic is better the students who are taught by using conventional.